Idarubicin-loaded drug-eluting microspheres transarterial chemoembolization for intermediate stage hepatocellular carcinoma - Koršič, Špela (Radiology and oncology (Ljubljana), 2024)
Background: Transarterial chemoembolization (TACE) is the treatment of choice for the intermediate stage hepatocellular carcinoma (HCC). Doxorubicin remains the most used chemotherapeutic agent in TACE, although in vitro screening has demonstrated that idarubicin exhibits greater cytotoxicity against HCC. This study aimed to evaluate safety, efficacy, and pharmacokinetics of idarubicin-loaded drug-eluting microspheres TACE (DEMIDA-TACE) in intermediate stage HCC patients. Patients and methods: Between September 2019 and December 2021, 31 consecutive intermediate stage HCC patients (96.8% cirrhotic) were included to this study. 2 mL of LifePearl™ microspheres (100 µm) loaded with 10 mg of 1 mg/mL idarubicin were used for treatment. The adverse events, objective response rate (ORR), progression free survival (PFS), time to TACE untreatable progression (TTUP), median overall survival (mOS), and pharmacokinetics were evaluated. Results: There were 68 TACE procedures performed. Adverse events grade ? 3 were noted after 29.4% procedures. The ORR was 83.9%, median PFS and TTUP were 10.5 months (95% CI: 6.8-14.3 months) and 24.6 months (95% CI: 11.6-37.6 months), respectively. Median OS was 36.0 months (95% CI: 21.1-50.9 months). Significant differences between patients achieving objective response (OR) and those with progressive disease were observed regarding idarubicinol and combined idarubicin-idarubicinol plasma concentrations at 72 hours post-procedure, higher plasma concentrations were observed in patients achieving OR (p = 0.014 and 0.014; cut-off values 1.2 and 1.29 ng/mL, respectively). Conclusions: DEMIDA-TACE emerges as a safe and effective method of treatment for the intermediate stage HCC with low rates of adverse events alongside high tumor response, favourable disease control and overall survival. Idarubicinol and combined idarubicin-idarubicinol plasma concentrations at 72 hours post-procedure may serve as prognostic factors for achieving OR.
Keywords: farmakokinetika; hepatocelularni karcinom; idarubicin; transarterijska kemoembolizacija mikrosfer, ki izločajo zdravilo; učinkovitost; varnost